Numerical validation of experimental heat transfer coefficient with SiO2nanofluid flowing in a tube with twisted tape inserts - Azmi, W.H. (Elsevier Ltd, 2014)
A numerical model has been developed for turbulent flow of nanofluids in a tube with twisted tape inserts. The model is based on the assumption that van Driest eddy diffusivity equation can be applied by considering the coefficient and the Prandtl index in momentum and heat respectively as a variable. The results from the numerical analysis are compared with experiments undertaken with SiO2/water nanofluid for a wide range of Reynolds number, Re. Generalized equation for the estimation of nanofluid friction factor and Nusselt number is proposed with the experimental data for twisted tapes. The coefficient and the Prandtl index in the eddy diffusivity equation of momentum and heat is obtained from the numerical values as a function of Reynolds number, concentration and twist ratio. An enhancement of 94.1 in heat transfer coefficient and 160 higher friction factor at Re = 19,046 is observed at a twist ratio of five with 3.0 volumetric concentration when compared to flow of water in a tube. A good agreement with the limited experimental data of other investigators is observed with Al2O3and Fe3O4nanofluids indicating the validity of the numerical model for use with twisted tape inserts. Â© 2014 Elsevier Ltd. All rights reserved.